Failure to infect laboratory rodent hosts with human isolates of Rodentolepis(= Hymenolepis) nana - MacNish, M.G.; Morgan, U.M.; Behnke, Jerzy M.; Thompson, R.C.A. (Cambridge University Press, 2002)
Confusion exists over the species status and host-specificity of the tapeworm Rodentolepis (= Hymenolepis) nana. It has been described as one species, R. nana, found in both humans and rodents. Others have identified a subspecies; R. nana var. fraterna, describing it as morphologically identical to the human form but only found in rodents. The species present in Australian communities has never been identified with certainty. Fifty one human isolates of Rodentolepis (= Hymenolepis) nana were orally inoculated into Swiss Q, BALB/c, A/J, CBA/CAH and nude (hypothymic) BALB/c mice, Fischer 344 and Wistar rats and specific pathogen free (SPF) hamsters. Twenty four human isolates of R. nana were cross-tested in flour beetles, Tribolium confusum. No adult worms were obtained from mice, rats or hamsters, even when immunosuppressed with cortisone acetate. Only one of the 24 samples developed to the cysticercoid stage in T. confusum; however, when inoculated into laboratory mice the cysticercoids failed to develop into adult worms. The large sample size used in this study, and the range of techniques employed for extraction and preparation of eggs provide a comprehensive test of the hypothesis that the human strain of R. nana is essentially non-infective to rodents.